2013
DOI: 10.1590/s1984-29612013005000021
|View full text |Cite
|
Sign up to set email alerts
|

Trypanoxyuris (Paraoxyuronema)lagothricis (Nematoda: Oxyuridae) in Lagothrix cana (Primates: Atelidae) from Brazil

Abstract: During necropsy of a specimen of Lagothrix cana (É. Geoffroy, 1812) (Primates: Atelidae) from the Brazilian Amazon, pinworms were found in the large intestine. The intensity of infection was 64 parasites (17 males and 47 females) and there were no gross pathological changes related to parasitism. After morphological analysis the parasites were identified as Trypanoxyuris (Paraoxyuronema) lagothricis (Buckley, 1931) (Nematoda: Oxyuridae). This is the first record of this oxyurid species in primates in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
2
4
0
1
Order By: Relevance
“…can be distinguished easily from T. (T.) callicebi and T. (T.) croizati , which have a hexagonal shaped cephalic-tray and a mouth opening bounded by three lips that partially cover the teeth. We also emphasize a small ornate subtooth in the ventral part of each oesophageal tooth, as reported in the studies by Hugot et al (1996) and Pinto et al (2013), and now observed in detail through scanning microscopy of our specimens.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…can be distinguished easily from T. (T.) callicebi and T. (T.) croizati , which have a hexagonal shaped cephalic-tray and a mouth opening bounded by three lips that partially cover the teeth. We also emphasize a small ornate subtooth in the ventral part of each oesophageal tooth, as reported in the studies by Hugot et al (1996) and Pinto et al (2013), and now observed in detail through scanning microscopy of our specimens.…”
Section: Discussionsupporting
confidence: 87%
“…The close evolutionary relationship between humans and other primates means that their parasite faunas are also similar and the possibility of cross-infection makes the identification of new species relevant to human medicine. In recent years the number of known species in the genus Trypanoxyuris has increased, adding Trypanoxyuris (P.) lagothricis and Trypanoxyuris (T.) minutus (Souza et al, 2010; Trejo-Macías et al, 2011; Pinto et al, 2013), which show interesting morphological variation and different geographical ranges compared to previously known species, such as Trypanoxyuris (T.) croizati and T. (T.) callicebi (Hugot et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that investigators have reported a different species of Trypanoxyuris as a parasite of Lagothrix lagotricha, i.e., T. lagothricis Buckley, 1931 [22,28], and that host-specificity has been argued to be a general feature for oxyurids infecting primates, where a pinworm species is often specific to one genus of primates [10].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Esses dados estão de acordo com aqueles descritos por Tavela et al (2013), que afirmam ser esse um dos helmintos mais frequentes nesse gênero de primata. Em bugios (Alouatta guariba), o helminto mais prevalente foi Trypanoxyuris minutus (77,8%), o qual costuma ser frequentemente relatado em estudos realizados com primatas, como pôde ser observado por Amato et al (2002) e Pinto et al (2013).…”
Section: Resultsunclassified